The Combination of Bay Leaf (Syzgyum polyanthum) and Noni Fruit (Morinda citrifolia) in Lowering Cholesterol Levels in Balb/C Hypercholesterolemia Mice - Noor, Ainullatiffah; Nanik Lestariningsih; Lilin Ika Nur Indahsari (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Central Kalimantan is rich in natural resources of potential medicinal plants, such as bay leaf and noni. These medicinal plants have been used traditionally. However, there is minimal scientific evidence about their use as a medicine due to limited research. The current research aims to identify the influence of applying a combination of bay leaf and noni fruit extract in lowering cholesterol levels in Balb/c hypercholesterolemic mice. The research employs a mixed method, namely explorative and experimental research. The research subjects are 28 female Balb/c mice in a hypercholesterolemic condition. The research consists of 7 treatments, namely positive control, negative control, P1 (20%), P2 (30%), P3 (40%), P4 (50%), and P5 (60%) with 4x repetitions. It combines the extract of bay leaf and noni fruit to lower cholesterol levels in the research subjects. Data analysis uses one-way ANOVA. The research results indicate that the application of a combination of bay leaf and noni fruit extract has a significant influence on the reduction of cholesterol levels in hypercholesterolemic mice with a p-value Î± (Î± 0.05) of 0.000. The concentration effective in lowering the cholesterol levels in hypercholesterolemic mice is in concentration P7 (60%) with a reduction of 59.25 mg/dL.